Native species germplasm banks and their role in ecological restoration: approaches and conclusions from the 1st International Symposium on Restoration Practices (Semiárida, 2025)
In November 2023, a workshop was held in Neuquén (Argentina) during the I International Symposium on Ecological Restoration Practices and the III National Ecological Restoration Meeting. The objective was to discuss the role of germplasm banks in ecological restoration. The experience, organized by the Argentine Network of Germplasm Banks of Native Plants (Red ARGENA), consisted of an interactive activity where the following questions were discussed: What do germplasm banks contribute to ecological restoration? Why conserve native species? What challenges or limitations do you face in the conservation of seeds for ecological restoration, and what strategies do you have to address them? The workshop included the participation of various social actors (nursery growers, students, researchers, and professionals/restorers). The analysis of the responses to the first question using a "word cloud" highlighted terms such as seeds and species (with 14 mentions), conservation (12), knowledge (10), genetics and restoration (9), among others. The reasons for conserving native species were grouped into five categories: they provide ecosystem services, prevent ecosystem degradation, avoid information loss, have use value, and adapt to different climatic and environmental conditions. The main challenges raised were the lack of material (native seeds) in quantity and quality, and the absence of knowledge or standardized protocols in the process. From the development and analysis of this workshop, we conclude that: a) ecological restoration is a cross-cutting issue in different fields, disciplines, and interests, b) germplasm banks are crucial for providing native species seeds, conserving genetic diversity, and generating knowledge necessary for restoration, and c) inter-institutional collaboration is a valuable tool to address the difficulties in the conservation of native species. This work highlights the importance of improving the technical and infrastructural capacity of seed banks and strengthening inter-institutional ties to meet the growing demand for seeds for ecological restoration.
Keywords: biodiversity; conservation; network ARGENA; seeds